Comparison of Nulliparas Undergoing Cesarean Section in First and Second Stages of Labour: A Prospective Study in a Tertiary Teaching Hospital - Ayhan Sucak; Şevki Çelen; Eren Akbaba; Sunullah Soysal; Ozlem Moraloglu; Nuri Danışman (Obstetrics and Gynecology International)
Objective. We performed a prospective observational audit study to compare neonatal and maternal outcomes of the primary cesarean sections performed in first stage versus second stage of labour. Methods. One thousand three hundred and eighty-nine nullipara women who had undergone cesarean section in a tertiary teaching hospital between February 1, 2009 and January 31, 2010 were included in the study. Primary maternal outcomes of interest were uterine atonia, transfusion requirement, urinary system injury, requirement for hysterectomy, and duration of hospital stay. Results. A total of 1389 women underwent cesarean section at this 12 month time period. Of these 1389 cesarean sections, 1271 were in the first stage of the labour and 171 were in the second stage of the labour. Urinary injuries, transfusion requirement, and uterine atonia hysterectomy were significantly more frequent in women who underwent cesarean section in the second stage of the labour compared to women undergoing cesarean section in the first stage of the labour. Conclusion. Cesarean section in the second stage of the labour is associated with increased maternal and neonatal morbidities. Special attention is required to the patients undergoing cesarean section in the second stage of the labour.